Aplikasi sistem informasi penjualan kue berbasis netbeans - Ida Fitriani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Septa Sari shop is a shop located on Jalan Kranggan, West Java that sells various types of bread and cakes. Septa Sari still uses a manual system in the aspects of ordering and business transactions. Some of the problems that exist include the ordering process and transactions that still have to be written in the book, and product data that has been ordered and sold has not been stored in the correct database. This allows the data to be damaged or lost. For this reason, the purpose of this research is to design an information system to be able to print the required reports on a regular basis. The research method used is a data collection method in the form of library research and field studies as well as the waterfall method. The result of this research is a Java Netbeans-based sales and ordering application using a MySQL database.